A hybrid fuzzy investment assessment framework for offshore wind-photovoltaic-hydrogen storage project. (January 2022) - Guo, Fengjia; Gao, Jianwei; Liu, Huihui; He, Pinglin
Highlights: A group decision framework is constructed for the investment of OWPH projects An S-shaped utility based PROMETHEE method is proposed to rank alternatives An investment assessment criteria system is established including 16 indicators A relative entropy-based model is built to calculate the importance of DMs A criteria weighting model is built involving DEMATEL and maximizing deviation idea Abstract: The offshore wind power-photovoltaic-hydrogen storage (OWPH) system has been considerably valued due to its advantages in improving power quality and increasing the absorption capacity of renewable energy power generation. To promote the rapid development and smooth implementation of the OWPH system, constructing a scientific investment decision-making framework is of utmost significance. Firstly, a criteria system that includes economy, resource, environment and support conditions, is established, where probabilistic hesitant fuzzy elements are introduced to depict the quantitative indicators and hesitant fuzzy linguistic term sets are employed by decision-makers to evaluate qualitative indicators. Then, a relative-entropy-based model is built to calculate the importance of decision-makers and a weighting model combining probabilistic linguistic-DEMATEL with the idea of maximizing deviation method is also built to compute the criteria weights. Moreover, an S-shaped utility-based PROMETHEE method is proposed to determine the optimal investment alternative(s). Finally, the proposed framework is applied in a case study to certificate the feasibility. The results illustrate that scheme A2 possesses the optimal comprehensive performance and the ranking order may vary with the change of decision-makers' risk attitudes. This research provides investors with scientific decision reference and also extend the methods in the decision-making field.